Presence of growth/differentiation factor-15 cytokine in human follicular fluid, granulosa cells, and oocytes - Souček, Karel; Malenovská, Alice; Kahounová, Zuzana; Remšík, Ján; Holubcová, Zuzana; Soukup, Tomáš; Kurfürstová, Daniela; Bouchal, Jan; Suchánková, Tereza; Slabáková, Eva; Hampl, Aleš (Journal of assisted reproduction and genetics, 2018)
Purpose The purpose of the study was to determine whether the GDF-15 is present in follicular fluid; to evaluate if there is a relation between follicular and serum levels of GDF-15 and fertility status of study subjects; and to test whether granulosa cells, oocytes, or both produce GDF-15. Methods This study used follicular fluid (FF, serum, and oocytes obtained under informed consent from women undergoing oocyte retrieval for in vitro fertilization. It also used ovaries from deceased preterm newborns. Collection of FF and blood at the time of oocyte retrieval, ELISA and western blot were performed to determine levels and forms of GDF-15. Concentrations of GDF-15 in FF and serum, its expression in ovarian tissue, and secretion from granulosa cells were analyzed. Results GDF-15 concentration in FF ranged from 35 to 572 ng/ml, as determined by ELISA. Western blot analysis revealed the GDF-15 pro-dimer only in FF. Both normal healthy and cancerous granulosa cells secreted GDF-15 into culture media. Primary oocytes displayed cytoplasmic GDF-15 positivity in immunostained newborn ovaries, and its expression was also observed in fully grown human oocytes. Conclusions To the best of our knowledge, this is the first documentation of cytokine GDF-15 presence in follicular fluid. Its concentration was not associated with donor/patient fertility status. Our data also show that GDF-15 is expressed and inducible in both normal healthy and cancerous granulosa cells, as well as in oocytes.